Trabajo y vida indígenas en los trapiches del Nuevo Reino de Granada, 1576 – 16741 (2017)
ABSTRACT: By a Crown´s rule, native workforce was forbidden inside the trapiches and sugar mills. Nonetheless, some Crown´s employees of the New Kingdom of Granada, in particular chief magistrates, avoided exerting this prohibition drastically, and allowed many indigenous people of encomiendas to pay their tributes with their labor on sugar production. This article studies both the reasons of this permissiveness and the changes that working on the trapiches generated among natives, especially those aspects linked to their community life and their consumption habits.